2018
DOI: 10.1002/2211-5463.12393
|View full text |Cite
|
Sign up to set email alerts
|

Identification of NADPH oxidase family members associated with cold stress in strawberry

Abstract: NADPH oxidase is encoded by a small gene family (Respiratory burst oxidase homologs, Rbohs) and plays an important role in regulating various biological processes. However, little information about this gene family is currently available for strawberry. In this study, a total of seven Rboh genes were identified from strawberry through genomewide analysis. Gene structure analysis showed the number of exons ranged from 10 to 23, implying that this variation occurred in FvRboh genes by the insertion and distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 49 publications
8
58
0
Order By: Relevance
“…In this study, a genome-wide identification and manual curation were performed, which results in seven Rboh family genes from both species. The family number is same as that present in grape and strawberry, but relatively smaller than other angiosperm plants reported thus far (Sagi & Fluhr, 2006;Cheng et al, 2013;Wang et al, 2013;Chang et al, 2016;Hu et al, 2018;Zhang et al, 2018;. The result is consistent with the fact that both jatropha and castor bean didn't experience any recent WGD, which act as a main force for expansion of genes or gene families (Qiao et al, 2019;Zou et al, 2016aZou et al, , 2017, 2019c.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, a genome-wide identification and manual curation were performed, which results in seven Rboh family genes from both species. The family number is same as that present in grape and strawberry, but relatively smaller than other angiosperm plants reported thus far (Sagi & Fluhr, 2006;Cheng et al, 2013;Wang et al, 2013;Chang et al, 2016;Hu et al, 2018;Zhang et al, 2018;. The result is consistent with the fact that both jatropha and castor bean didn't experience any recent WGD, which act as a main force for expansion of genes or gene families (Qiao et al, 2019;Zou et al, 2016aZou et al, , 2017, 2019c.…”
Section: Discussionsupporting
confidence: 85%
“…Manuscript to be reviewed esculenta), ten members from arabidopsis (Arabidopsis thaliana), ten members from rubber (Hevea brasiliensis), and 15 members from wheat (Triticum aestivum) (Sagi & Fluhr, 2006;Cheng et al, 2013;Wang et al, 2013;Hu et al, 2018;Zhang et al, 2018;. Evidence showed that RBOHs play key roles in growth, development, hormone signaling, and stress responses of plants (Marino et al, 2012;Kaur et al, 2014;Angelos & Brandizzi, 2018;Wang et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…NADPH oxidases, also named respiratory burst oxidase homologues (RBOHs), require NADPH to generate the superoxide anion (O 2 - ), subsequently ending with the secondary production of other ROS such as hydrogen peroxide (H 2 O 2 ) [ 41 ]. Our previous study demonstrated that RBOHD was important in response to cold stress in strawberry [ 42 ]. As shown in Figure 6 K and Figure 7 K, the expression of FaRBOHD was markedly increased under cold treatment, and significantly higher in overexpressing FaG6PDH-CY than that in control.…”
Section: Discussionmentioning
confidence: 99%
“…AtSRC2 is an activator of Ca 2+ -dependent AtRbohF-mediated ROS production and may play a role in cold responses [126]. Similarly, a recent study proposed that the expression levels of FvRbohA and FvRbohD in strawberry are quickly induced by cold, followed by an increase in NADPH oxidase activity [127]. Conversely, at high temperature (30°C), the total NADPH oxidase activity and NtRbohD expression are all suppressed in tobacco mosaic virus (TMV)-inoculated leaves of tobacco, which resulted in less ROS production and enhanced susceptibility to pathogen and suppression of HR-type necrosis [128,129].…”
Section: Temperature Responsementioning
confidence: 95%